IMPLEMENTATION OF INFRASTRUCTURE PROJECTS FOR THE DEVELOPMENT OF RAILWAY TRANSPORT HUBS: EMPIRICAL ANALYSIS - P. S. Kuzmin (Стратегические решения и риск-менеджмент, 2023)
The key tool for economic growth and overcoming restrictions is the implementation of major infrastructure projects in the field of railway transport. Infrastructure projects aimed at organising passenger and freight rail traffic form a wide range of social effects, such as saving travel time, improving transportation safety, reducing emissions of harmful substances and noise levels, increasing physical activity, improving social integration and organising a barrier-free environment, agglomeration effects and an increase in subjective well-being.At the same time, such projects are very capital-intensive and often cannot be implemented in full due to limited funding. Especially this factor plays a significant role in the current conditions of sanctions pressure. The combination of these factors leads to the need for comprehensive risk management when deciding on the implementation of an infrastructure project for the development of railway junctions.Thus, the purpose of this study is to identify risks in the implementation of infrastructure projects, assess the identified risks and formulate recommendations for their reduction.